Plataforma coletivo: a construção de uma plataforma digital de design thinking para profissionais da economia criativa - Ribeiro, Vivian Souza (2022)
For this research, design thinking is understood as an approach that can help professionals in the creative economy, not project specialists, to develop inventive solutions through ideas such as collaboration and human-centeredness. Such an approach proposes different methods and techniques in order to guide the creation of technologies that are accessible and viable, both strategically and economically. In order to encourage the development of solutions with professionals in the creative economy, the Coletivo (collective, in Brazilian Portuguese) platform was created, and you can find its development process and theoretical foundation described in this work. The platform includes a catalog of tools and design thinking content. It also facilitates a network for creative professionals, who can act as collaborators, mentors or investors with other users in the development of solutions. Such theoretical foundation includes concepts from the areas of social design, interaction design and design thinking, which helped in the construction of the product's content and interface. In addition, aspects of the context of creative economy professionals, talking about intellectual property and the formation of networks through the internet, were addressed. As a result of this process, a high-fidelity prototype of the platform was obtained. To this end, bibliographic research was carried out, in addition to field research that includes methods and techniques specific to the field of design. A card sorting, a usability test with a low-fidelity prototype, and the application of the method with cultural probes were carried out, in which the participants wrote down in diaries over the course of a week about their experience with the product in this research. Thus, it was possible to assimilate improvements in case the platform is implemented, as well as reflections on creativity and on the field of design.